(untitled) (Scientific journal of the Fergana State University, 2023)
The article explores the historical and philosophical essence of Sufism, its place in Islamic culture and civilization, along with the of the formation of high spirituality, religiosity and moral values of the individual, and analyzes the current state of sufism in Uzbekistan.